The Global Longitudinal University Enrollment Dataset (GLUED) - Buckner, Elizabeth (International Higher Education, 2022)
Existing cross-national data on higher education participation has many limitations: It is collected primarily at the national level, combines short-cycle tertiary education with university enrollments, and lacks disaggregated data on the private sector before 1998. The Global Longitudinal University Enrollment Dataset (GLUED) seeks to address these limitations. The dataset compiles and estimates institution-level enrollment data on universities worldwide from 1950 to 2020. This article discusses the advantages that GLUED offers researchers of higher education.